5 Решите уравнение, введением новой переменной:
2√3 х+5√6 х - 3=0

neleachibzii neleachibzii    1   25.11.2021 10:34    1

Ответы
Zebra1411 Zebra1411  25.11.2021 10:40

х=-1,5±0,5√5;

пусть х²+3х=а,

тогда (а+3)*(а+1)=0

а*а +3*а +а*1 +3*1=0

а² +3а+а+3=0

а²+4а+3=0

D=4²-4*1*3=16-12=4=2²

a1=(-4+2) / (2*1) = -2/2 = -1

a2=(-4-2) / (2*1) = -6/2 = -3

выход из замены: а=х²+3х

1) х²+3х=-1

х²+3х+1=0

D=3²-4*1*1=9-4=5=(√5)²

x1=(-3+√5)/(2*1) = -1,5 + 0,5√5

x2=(-3-√5)/(2*1) = -1,5 - 0,5√5

2)х²+3х=-3

х²+3х+3=0

D=3²-4*3*1=9-12=-3<0 — нет решений

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра